PENGARUH LITERASI KEUANGAN, TINGKAT PENGEMBALIAN DAN PERSEPSI RISIKO TERHADAP PENGAMBILAN KEPUTUSAN INVESTASI PASAR MODAL PADA GEN Z DI SUKABUMI - Amanda, Mila; Wulandari, Try (Universitas Mercu Buana, 2025)
This study aims to analyze the extent to which financial literacy, rates of return, and risk perception influence investment decisions in the capital market among Gen Z in Sukabumi City. The study used a causal design with a population of 93,077 Gen Z individuals, while the research sample was determined at 100 respondents through the Slovin formula calculation. Data analysis was carried out using the SEM-PLS. The results of the study show that: (1) Financial literacy has a positive and significant influence on investment decisions, indicating that the better a person's financial understanding, the higher their tendency to invest. (2) The rate of return also proved to have a positive and significant influence, confirming that potential profits are the main driving factor for Gen Z in making decisions. (3) Risk perception shows a positive and significant influence on investment decisions, which means that the greater the awareness of risk, the higher the investor's confidence in determining their investment choices.